ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN GAME EDUKASI BERBASIS WORDWALL PADA MATERI KOSAKATA BAHASA INGGRIS KELAS IV - Aulia Wuri Ramadhani; Erwin Rahayu Saputra; Muhammad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the need for educational game-based learning media using the Wordwall platform in teaching English vocabulary to fourth-grade elementary school students. The research responds to the observed limitations in current instructional practices, which are still dominated by conventional methods and printed textbooks, resulting in low student motivation and limited vocabulary mastery. Using a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews with teachers, and documentation analysis at two elementary schools in Tasikmalaya, Jawa Barat. The findings indicate that while the Wordwall platform is available and occasionally used, its implementation is inconsistent and not specifically focused on vocabulary development. Teachers mainly rely on printed textbooks, and digital resources are underutilized, despite the availability of supporting infrastructure. Student exhibited interest and enthusiasm when exposed to interactive and game-based media, suggesting that such tools have strong potential to enhance vocabulary learning. This study highlights the urgency of developing creative, efficient, and pedagogically sound Wordwall-based materials that align with learners’ needs. The results serve as a foundation for future research and development in the creation of innovative digital vocabulary learning resources for primary education.